Integrated ABC–VED–AHP Framework for Prioritizing Returned Materials in Electricity Transmission Warehouse Management - Adianto, Muhammad Dias Rizal; Arvitrida, Niniet Indah (UNIPA PRESS, 2026)
Returned materials in electricity transmission warehouses represent ex-operational assets that may still contain economic value and operational utility. However, their accumulation can reduce warehouse efficiency, increase storage burden, and delay asset recovery decisions. In PT PLN (Persero) transmission warehouses, warehouse capacity utilization reached an average of 93.29%, exceeding the recommended operational threshold, with several warehouses experiencing overcapacity conditions. Existing classification practices remain administrative and do not provide a systematic basis for determining whether materials should be retained, repaired, reused, transferred, or disposed of. This study proposes an integrated multi-criteria decision framework for prioritizing returned materials by combining ABC analysis, VED analysis, physical condition assessment, reuse potential evaluation, and the Analytic Hierarchy Process (AHP). The framework was applied to 580 returned material items with a total replacement value of IDR 256,057,003,073. The AHP results show that operational criticality is the most influential criterion with a weight of 0.5342, followed by physical condition, economic value, and reuse potential. The consistency ratio was 0.0455, indicating consistent expert judgment. The final prioritization classified 397 items as high priority, 116 items as medium priority, and 67 items as low priority. The proposed framework supports more objective, transparent, and data-driven decision-making in returned material management and contributes to warehouse space optimization, dead stock reduction, and asset recovery improvement in electricity infrastructure systems.